Genotypic and phenotypic characterization of foodborne Geobacillus stearothermophilus. (February 2015) - Durand, Loïc; Planchon, Stella; Guinebretiere, Marie-Hélène; Carlin, Frédéric; Remize, Fabienne
Abstract: Geobacillus stearothermophilus is the main thermophilic spore former involved in flat sour spoilage of canned foods. Three typing methods were tested and applied to differentiate strains at intra-species level: panC sequence analysis, REP-PCR and M13-PCR. panC gene was highly conserved within the studied strains, suggesting a low intra-specific diversity. This was supported by REP-PCR primary assays and M13-PCR results. M13-PCR profile analysis succeeded in differentiating six closely related groups (at 79% threshold similarity) among 127 strains from a range of spoiled canned food products and from different canneries. Phenotypic traits were investigated among 20 selected strains representing groups and origins. Ranges of growth under different temperatures (from 40 °C to 70 °C), pH (from 5.0 to 6.5), NaCl concentrations (from 1 to 5%) and sporulation conditions poorly differed between strains, but wet heat resistance of spores showed a 20-fold variation between strains. Furthermore, in this study, strains that belonged to the same M13-PCR genetic group did not share phenotypic characteristics or common origin. The work emphasizes a low diversity within the G. stearothermophilus species but data from this study may contribute to a better control of G. stearothermophilus spoilage in canned food. Highlights: 127 Geobacillus stearothermophilus strains of diverse origins were examined for diversity. M13-PCR typing showed a weak genetic diversity. Growth limits for temperature, pH and NaCl poorly differed between strains. Time to 5 log-reduction varied between <0.5 min and 12.4 min.